Women and cardiovascular disease : addressing disparities in care - Campbell, Kevin R. (Imperial College Press, 2015)
Cardiovascular disease is the number one killer of both men and women in the US and Europe today. Over the last 20 years, many innovations in technology have allowed for improved therapies for heart attack and stroke and overall outcomes have significantly improved. Death rates from cardiovascular disease in men are declining. However, even with these improvements in care, death rates for women remain unchanged. This book will explore these gender disparities in care in depth - specific sections will be devoted to answering the questions of why they are occurring and what healthcare providers and women can do to effect change and narrow the gender gap in cardiovascular care. Ultimately, this book is designed to open the eyes of healthcare providers, medical professionals and policy makers - as well as potential female patients - and should serve as a "call to action" to promote better cardiovascular care for women. Through education, awareness and advocacy women worldwide will benefit, the gap will begin to close and better cardiovascular care can be provided for all